The challenges of managing malignant head and neck tumors in a tropical tertiary health center in Nigeria - Adeyi, Adoga (The African Field Epidemiology Network, 2011)
INTRODUCTION: In developing countries, factors such as late patient presentation, inaccessible and limited health facilities contribute to the poor outcome in the management of patients with head and neck malignant tumors. This study presents the challenges faced by the otorhinolaryngologist in our environment in the management of patients with head and neck malignant tumors. METHODS: This is a ten-year retrospective chart review of patients with histopathologically confirmed head and neck malignancies in the Jos University Teaching Hospital, Jos, Nigeria. RESULTS: Eighty nine patients, with male predominance (gender ratio of 2.7:1) aged between 23 and 78 years had head and neck malignancies. Eighty eight (99%) patients had histopathological diagnosis. Most patients were from rural areas and had seen the herbalist prior to presentation. Thirty four (38.2%) patients were in the 4th decade of life. Eighteen (20.2%) patients presented within 6 months of onset of illness and 71 (79.8%) patients after 6 months with 38/89 patients having cervical lymphadenopathy at presentation. Four (4.5%) patients were able to afford CT scan. Twenty eight deaths were recorded. Ten patients were lost to follow-up. CONCLUSION: The challenges faced in managing patients with head and neck malignant tumors in our environment are enormous but surmountable. Therefore urgent efforts should be made by health workers and government to ensure a better outcome for these patients.